The Impact of Strengthened Tax Enforcement on Corporate Cash Holdings: A Review of Literature and Empirical Evidence - Yessica Amelia; Muhammad Rizal (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
This qualitative literature review examines the impact of strengthened tax enforcement on corporate cash holdings, synthesizing findings from recent empirical studies. The review highlights that enhanced tax enforcement prompts firms to adopt precautionary cash management strategies, often resulting in higher cash reserves to mitigate tax-related risks. Key factors influencing this relationship include firm size, governance quality, industry characteristics, and jurisdictional tax policies. Cross-country comparisons reveal significant variations, with institutional frameworks playing a crucial role in shaping corporate responses. While stricter enforcement ensures compliance, it may inadvertently constrain investment and operational efficiency due to increased liquidity demands. This study underscores the complexity of corporate financial decision-making under tax enforcement pressures and identifies gaps for future research, particularly in emerging markets.